Smart technologies and the future of concussion prevention in ice hockey - Gråstén, A. (Frontiers in Sports and Active Living, 2025)
Background: Concussions in ice hockey remain a major concern, especially among young players. Current helmets mainly protect against skull fractures but offer limited shielding from brain acceleration forces.